2023
DOI: 10.3390/catal13050811
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in N-Heterocyclic Carbene Coinage Metal Complexes in A3-Coupling and Carboxylation Reaction

Abstract: Owing of their accessibility and wide range of reactivities, alkynes make for fascinating building blocks. Either a selective alkyne carbon-carbon triple bond reaction or activation of the terminal alkyne C-H bond may be employed to functionalize them. Monocationic coinage metal complexes with a d10 electronic configuration are effective catalysts for alkyne activation. Silver(I) and gold(I) N-heterocyclic (NHC) systems are emerging as promising catalysts in multicomponent alkyne activation reactions; this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…1B). 19–22 However, our recent findings, 23 as well as other studies, have revealed the possibility of silver( i ) atom chelation by bidentate ligands (Fig. 1C).…”
Section: Introductionmentioning
confidence: 47%
See 1 more Smart Citation
“…1B). 19–22 However, our recent findings, 23 as well as other studies, have revealed the possibility of silver( i ) atom chelation by bidentate ligands (Fig. 1C).…”
Section: Introductionmentioning
confidence: 47%
“…1A). 18–20 The structural diversity is further expanded with the use of bidentate ligands. In most instances, each NHC moiety coordinates to a different silver( i ) atom, potentially leading to dimeric neutral or cationic monomeric species (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The field of metal-catalyzed four-component coupling reactions towards oxazolidinone synthesis is rapidly evolving, [5] but most of the catalytic systems are based on Cu(I) [6] (few contributions involve Cu(II) catalytic precursors [7] ) or combinations thereof with engineered solvents such as ionic liquids to enhance the recyclability of the resulting catalytic systems. [8] From a mechanistic point of view, the seminal work reported by Li and coworkers proposed a mechanism for the A 3 -coupling carboxylative cyclization through the formation of the corresponding propargylamine intermediate and also pointing to a synergistic effect between the amine and CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Under a chemical point of view, Au(I)/Ag(I) NHC complexes are effective catalysts for some coupling reactions, such as a three-component condensation among an aldehyde, an amine, and a terminal alkyne, named the A 3 -coupling reaction, hydroamination, or alkoxylation of alkynes to produce imine or enol, respectively. Thus, the catalytic activity of new synthesized compounds was also evaluated both in A 3 -coupling and in hydroamination reactions [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%